P10 Asbestos-induced diffuse pleural thickening—a continuing problem. (16th November 2010) - Jeebun, V; Stenton, SC
Abstract : Introduction: Asbestos-induced diffuse pleural thickening (DPT) remains a relatively common but poorly understood disease. Methods: We reviewed the clinical, physiological and radiological features of patients referred to our department for assessment. Diagnosis was based on a history of asbestos exposure, chest radiographic pleural thickening with blunting of costophrenic angle, and exclusion of other likely causes of pleural disease. Results: 75 patients were identified. All were male. Mean age was 65±9 years. Asbestos exposures occurred in shipyards (n=35), construction work (n=19), power stations (n=4) and other/multiple sites(n=17). Median duration of asbestos exposure was 13 years. Presentation occurred at a median of 36 years (range: 12–55 years) after onset of exposure. Pleural disease was an incidental radiological finding in 18% (n=14). 72%presented with breathlessness, 27% with chest pain, and 11% had flu-like symptoms. 40% (n=30) presented with a pleural effusion, which was suspected to be asbestos-related. Mean latency for development of pleural effusions was 31 years (range: 12–55 years). 24 of these were unilateral only, and 6 were bilateral. Right-sided effusions were five times more prevalent than left-sided effusions. After the diagnosis of a pleural effusion, DPT was noted radiologically after a median of 7 months (range: 1 month to 2 years). In 10% (n=3), the effusion persisted over a median follow-up period of 2 years. Overall, 73% (n=55) had unilateral disease at presentation and 24% (n=13) were observed to progress from unilateral to bilateral disease after a mean time of 3.1±3.6 years (range: 1 month to 13 years) after onset of disease or diagnosis. Once established, the degree of thickening remained stable in 91% (n=68). There were no significant differences in either duration of asbestos exposures or latency in patients with stable versus progressive disease. No difference in duration of asbestos exposures was also found between those with unilateral versus bilateral disease. Most patients had restrictive abnormalities on lung function testing with mean TLC 74% and mean RV 73% of predicted. Radiographic appearances correlated poorly with lung function impairment or symptom progression. Conclusion: Understanding its natural history should help clinicians diagnose and manage asbestos-induced benign pleural thickening.